2018
DOI: 10.18203/2394-6040.ijcmph20181204
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of asthmatic respiratory complications among the rural community of Tangail area in Bangladesh

Abstract: Background: Asthmatic respiratory complications appear to be a notable public health consequence and associated with mortality, morbidity and economic burden worldwide. Globally several epidemiological studies have been conducted to assess the prevalence of asthmatic respiratory complications. As far our knowledge very few population based study have been conducted in Bangladesh to assess the magnitude of asthmatic respiratory complications focusing the rural community. Therefore the study was undertaken to as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Some other studies in Bangladesh also found that besides smoking and age, sex, socioeconomic status, occupation, eating behaviour and comorbidities were major risk factors in asthma outcome. 41 42 The role of family history was also shown to some extent in a previous study in rural Bangladesh. 42 43 A recent review article suggested that adult onset of asthma was linked with gender (females more than males), obesity, smoking habit, and low socioeconomic condition.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Some other studies in Bangladesh also found that besides smoking and age, sex, socioeconomic status, occupation, eating behaviour and comorbidities were major risk factors in asthma outcome. 41 42 The role of family history was also shown to some extent in a previous study in rural Bangladesh. 42 43 A recent review article suggested that adult onset of asthma was linked with gender (females more than males), obesity, smoking habit, and low socioeconomic condition.…”
Section: Discussionmentioning
confidence: 62%
“…The distribution of the proportion of asthma was shown to be associated with other variables but the results were not significant. Some other studies in Bangladesh also found that besides smoking and age, sex, socioeconomic status, occupation, eating behaviour and comorbidities were major risk factors in asthma outcome 41 42. The role of family history was also shown to some extent in a previous study in rural Bangladesh 42 43.…”
Section: Discussionmentioning
confidence: 70%
“…The questions about environmental exposure and socio-demographic profile were also asked in separate sections. The validity and reliability of the IUATLD questionnaire has been checked and quoted in many research works [25].…”
Section: Administered Respiratory Questionnairementioning
confidence: 99%